Acute-phase proteins in cats with obstructive feline lower urinary tract disease - Dinallo, Heloíse Rangel [UNESP]; Giuffrida, Rogério; de Azevedo, Maria Gabriela P. [UNESP]; Santarém, Cecília L.; Andrade, Silvia M. C. F.; Brinholi, Rejane B.; da Motta, Yudney Pereira; Schmidt, Elizabeth M. S. [UNESP]; Ferreira, João Carlos P. [UNESP]; García, Henry David M. [UNESP]; de Brito, Adriana Falco; Melchert, Alessandra [UNESP]; et al. (Wiley, 2022)
Background: Feline obstructive disease of the lower urinary tract (FLUTD) is a common pathologic condition of cats. It can be related to sterile inflammation, which leads to acute impairment of renal function and the accumulation of electrolytes and acid-base imbalance. Acute-phase proteins (APPs) are biomarkers of tissue damage from inflammation that assist in monitoring treatment and prognosis. Objective: Monitoring the inflammatory processes of obstructive feline lower urinary tract disease through the determination of plasma fibrinogen concentrations and serum concentrations of the acute-phase proteins, serum amyloid A (SAA), alpha-1-acid glycoprotein (AGP), and albumin. Methodology: Twenty-five male cats were included in this study. They were divided into two experimental groups: a control group (CG) and an obstruction group (OG). There were 8 healthy cats in the CG group and 17 cats with obstructive FLUTD in the OG group. APP measurements were conducted using ELISA kits. Samples were collected for APP analyses, serum biochemical assays, urinalyses, and urine protein: creatinine ratio calculations at diagnosis, before urethral clearance (H0), and 12 (H12), 24 (H24), and 48 (H48) hours after urethral clearance from cats in the OG group. Samples were collected once from cats in the CG group cats. Results: At H0, we found positive correlations of SAA, AGP, and fibrinogen with urea and creatinine, and negative correlations of albumin with hematuria, SAA, and potassium. At H48, we found positive correlations between SAA and AGP, AGP and urea, fibrinogen and urea, fibrinogen and creatinine, fibrinogen and AGP, and fibrinogen and SAA. In addition, a negative correlation of albumin with urea and creatinine was observed. Conclusions: Serum amyloid A, AGP, fibrinogen, and albumin could be used as biomarkers of inflammatory processes in cats with obstructive FLUTD.
Keywords: AGP; FLUTD; SAA